MAL – ADMINISTRASI DALAM PENYELENGGARAAN PENGELOLAAN PERPARKIRAN DI KOTA BUKITTINGGI - Ranty Isra Putri; Nur Laila Meilani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Law no. 37 of 2008 on the Ombudsman of the Republic of Indonesia clearly stipulates the duties and authority of the Ombudsman of the Republic of Indonesia namely to receive and complete reports on alleged Mal - Administration in the provision of public services. Lack of public awareness, the extent of illegal levies is a description of the current state of bureaucracy in Indonesia. Parking management is one of the social phenomenon in Bukittinggi City which is in need of government attention. The purpose of this research is to know how the forms and factors that influence the emergence of Mal - Administration and what efforts are made to overcome Mal - Administration in the management of parking in Bukittinggi City. The concept of theory used is Mal - Administration theory by Nigro and Nigro, namely dishonesty, bad behavior, ignoring the law, and favoritism in interpreting the law. This research uses qualitative research method with case study approach and data assessment is desktiptif. Technique of collecting data through interview technique, observation, library study and documentation by using purposive sampling method in informant selection. The result of the research is that the management of parking in Bukittinggi City needs to be maximized again, it is shown that the obligation and responsibility of parking management management has not been able to be implemented properly, the perception and the public response to the management of parking area need to be improved.Keywords: Mal – Administration, Parking Management, Public Service